I. Kant and Russian Symbolism: Criticism of the “Enchanted Distance” - Dmitry D. Romanov (RUDN Journal of Philosophy, 2024)
The research explores the ways of Kantianism reception in Russian symbolism philosophy. The emphasis is made on the philosophical systems of V.S. Solovyov, A. Bely, V.I. Ivanov and P.A. Florensky as the most holistically reflecting the development of epistemological, aesthetic, and general theoretical tendencies of the symbolist school, whose representatives are united by the similarity of critical positions regarding the teachings of I. Kant, which indicates the homogeneity of symbolist philosophy itself in its relation to transcendental idealism. The Kantian influence is analyzed, firstly, through the symbolist philosophy of culture disclosure and the influence of Marburg school neo-Kantianism on it, secondly, by identifying the foundations of the Silver Age mythocentric metaphysics with its unique ethical paradigm, thirdly, through solving the problem of antinomianism in the theory of cult as a space of religious creativity. Evolution peculiarity of Kantian influence on symbolism is explicated from the absolute acceptance of the criticism concepts of pure reason and the ability of judgment to their complete denial and search for the possibility of resolving antinomianism through the specific mission of social aesthetics. It is argued that with Kant's strong influence on the development of symbolist aesthetics, the symbolists themselves are looking for ways to bridge the gap between the world of noumenons and phenomena in it, noting the special role of theurgic creativity and the concept of catholicity consciousness. This makes it possible to understand the philosophy of symbolism as a counterargument system when posing the problem of the noumenal reality incomprehensibility. It is concluded that the symbolist criticism of Kantianism is generally religious and mystical-intuitionistic in general, justifying the possibility of comprehending the noumenal world as a principle of spiritual doing.